2017
DOI: 10.1002/jtr.2122
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of international employment levels in hospitality occupations using secondary statistics

Abstract: Frequent claims are made for the importance of the hospitality industry, and wider tourism sector, as potential and actual creators of employment. Many of these claims emanate from industry representative and advocacy organizations, often as part of their legitimate efforts to lobby governments for favourable treatment of their sectors. Good quality universal statistical data on employment in hospitality are noticeable by their absence, although information collected by bodies such as the International Labour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(28 reference statements)
0
8
0
1
Order By: Relevance
“…Frequent claims are made for the importance of the hospitality industry, and wider tourism one, as potential and actual creators of employment. Many of these claims emanate from industry representative and advocacy organizations, often as part of their legitimate efforts 59 AN ANALYSIS OF FOODSERVICE AND ACCOMMODATION Edyta Gheribi Alessandro Bonadonna to lobby governments for favorable treatment of their industries (Koens and Wood, 2017).…”
Section: Foodservice and Accommodation Sector -Sectoral Analysismentioning
confidence: 99%
“…Frequent claims are made for the importance of the hospitality industry, and wider tourism one, as potential and actual creators of employment. Many of these claims emanate from industry representative and advocacy organizations, often as part of their legitimate efforts 59 AN ANALYSIS OF FOODSERVICE AND ACCOMMODATION Edyta Gheribi Alessandro Bonadonna to lobby governments for favorable treatment of their industries (Koens and Wood, 2017).…”
Section: Foodservice and Accommodation Sector -Sectoral Analysismentioning
confidence: 99%
“…In forming a realistic impression of tourism and hospitality employment opportunities, it is important to have a true picture or the numbers in work. A recent paper by Koens and Wood () has provided a preliminary quantification by country and territory by mining a wide range of official statistics. They concluded that hospitality accounts for 4.6% of employment in Asia and 6.9% in North America.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ambas fuentes son utilizadas con frecuencia por la comunidad académica, sea para realizar un tratamiento estadístico de manera directa con estos datos (Hanafiah et al, 2016;Simas et al, 2017), o como información complementaria al análisis que realizan (Arshad et al, 2018;Koens & Wood, 2017). Por tanto, estas fuentes han sido escogidas atendiendo tanto a la consistencia de los datos, como a la normalización en la metodología de recopilación y almacenamiento.…”
Section: Materiales Y Fuentesunclassified